ANALISIS KORELASI ANTARA MOTIVASI KERJA DENGAN KUALITAS PELAYANAN PEGAWAI - Donani, Donani (PREDIKSI, 2016)
This study aims to determine the motivation and quality of service of the staff at Harapan Insani Hospital Sendawar Kutai Barat. Besides, this study also aimed to determine the correlation between work motivation and the quality of service of employees at Harapan Insani Hospital Sendawar Kutai Barat. The results showed that the product moment correlation coefficient (Pearson) of 0.408 at a significance level of 5%. The results of this analysis when compared with the prices Critical contained in table r Product Moment Correlation (Pearson) at a significance level of 5% to N = 130 by .170, then the value is greater than the empirical r r theoretical value or 0.408 > 0.170. Thus it can be concluded that there is a significant relationship of work motivation variable with the variable quality of service. The results showed also that the t-test results is equal to 5.051 at a significance level of 5%. While t-theoretical value as shown in the table t-test contained in the annex to this paper shows the value of t for n - 2 (130-2 = 128) amounted to 1,979. Thus it can be said that t-empirical (5.051) is greater than the t-theoretical (1,979). Thus, there are significant and significant relationship between work motivation with the variable quality of service.